Validity and Relative Ability of 4 Balance Tests to Identify Fall Status of Older Adults With Type 2 Diabetes. Issue 4 (October 2017) - Marques, Alda; Silva, Alexandre; Oliveira, Ana; Cruz, Joana; Machado, Ana; Jácome, Cristina
Abstract : Background and Purpose: The Berg Balance Scale (BBS), the Balance Evaluation Systems Test (BESTest), the Mini-BESTest, and the Brief-BESTest are useful tests to assess balance; however, their clinimetric properties have not been studied well in older adults with type 2 diabetes (T2D). This study compared the validity and relative ability of the BBS, BESTest, Mini-BESTest, and Brief-BESTest to identify fall status in older adults with T2D. Methods: This study involved a cross-sectional design. Sixty-six older adults with T2D (75 ± 7.6 years) were included and asked to report the number of falls during the previous 12 months and to complete the Activities-specific Balance Confidence scale. The BBS and the BESTest were administered, and the Mini-BESTest and Brief-BESTest scores were computed based on the BESTest performance. Receiver operating characteristics were used to assess the ability of each balance test to differentiate between participants with and without a history of falls. Results: The 4 balance tests were able to identify fall status (areas under the curve = 0.74-0.76), with similar sensitivity (60%-67%) and specificity (71%-76%). Conclusions: The 4 balance tests were able to differentiate between older adults with T2D with and without a history of falls. As the BBS and the BESTest require longer application time, the Brief-BESTest may be an appropriate choice to use in clinical practice to detect fall risk.